Perbandingan Latihan Two Kick One Pull dengan Controlled Breaststroke terhadap Stroke Rate Gaya Dada - Azzah Shabira Putri; Heru Miftakhudin; Ferry Yohannes Wattimena (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This study aims to find out, 1) The effect of exercise using two kick one pull on the stroke rate of breaststroke, 2) The effect of exercise using controlled breaststroke on the stroke rate of breaststroke, 3) The difference in stroke rate of breaststroke through the method of two kick one pull exercise with controlled breaststroke. This research method uses an experimental method with research using two groups